The Moderating Role of Financial Literacy on the Effects of Subjective Norms, Product Involvement, and Perceived Behavioral Control on Invest-ment Intention of Young Investors from a Mobile Wallet App in the Philippines - Tanpoco, Manuel; Katalbas, Rizal Ezmin III; Roxas, Rafael Raymond Phillip; An, Jeongwon; Orlina, Joshua Zachary (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
Investment has grown to be an industry of its own, becoming more diverse in portfolio, now not only in mutual funds and bonds, but now covering or blending with insurance, and growing in market size and reach extending to people who are yet to join the work force. Being an investor was made even more accessible through mobile wallet apps that allow individuals to start investing with just a few clicks of their cellphones. And, as this industry gets bigger, it becomes more important to determine the determining factors why young people start investing with their mobile wallet apps. This study aims to determine the moderating role of financial literacy on the effect of subjective norms, product involvement, and perceived behavioral control on investment intention of mobile wallet app users among the youth in the Philippines. An online survey was administered online to 407 young insurers from mobile wallet apps who are within the ages of 18 and 30. Moderated regression through path analysis determined that subjective norms, perceived behavioral control, and product involvement significantly affect the investment intention of young insurers. Further, financial literacy amplifies the effects of product involvement and subjective norms on investment intention. This research posits that educating people more to be financially literate will most likely lead to more people in the younger generation deciding to invest early for their future.